A study on parental age, pregnancy events and autism spectrum disorders - Malla, Aakriti; Pathak, John; Shrestha, Sanjeev; Pant, Aditi; Shrivastava, Trilok; Amatya, Sunita Malekhu; Joshi, Sunil Kumar (Journal of Kathmandu Medical College, 2017)
Background:Autism spectrum disorder (ASD) is a neurological disorder which usually appears before the age of 3. Several genetic or environmental factors may be involved in onset of Autism Spectrum Disorder. Objectives: To find relationship of Autism Spectrum Disorder with different maternal factors and events during pregnancy. Methodology: This is a retrospective case control study with total of 104 children of age 3-15 years as a sample, 52 were cases and 52 were controls. The study unit was selected from the database of Autism Care Nepal (ACN) for cases and questionnaire was designed based on the probable risk factors of Autism Spectrum Disorder from existing literature. Controls were chosen from schools, questionnaire being filled by asking questions to the mothers of the child with same age group as the cases, similar socio-economic background and intellectually normal. Results:There were 78.8% males and 21.1% females among cases and 53.8% were male and 46.1% were female among controls which show male predominance among cases. Among various maternal risk factors, the maternal second hand smoking (P value: 0.04) and maternal respiratory tract infection (P value: 0.04) were found to be statistically significant. Regarding neonatal factors, birth asphyxia (P value: 0.003), delayed cry (P value: 0.000) and neonatal jaundice (P value:0.05) were found to be statistically significant. Conclusion:We found association of maternal second hand smoking, respiratory tract infection and among neonatal factors, birth asphyxia, delayed cry and neonatal jaundice to be associated with Autism Spectrum Disorder. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017 editor@jkmc.com.np